Attention Deficit Hyperactivity Disorder (ADHD) and Public Stigma - คุ้มศิริ, ภาสกร; เล็กน้อย, อุ่นเรือน (Journal of Preventive Medicine Association of Thailand, 2018)
This article presents the knowledge about Attention Deficit Hyperactivity Disorder (ADHD) and public stigma to children with ADHD causing by their different behavior from the regular children in the same age. The obvious different behaviors include are a lack of concentration which negatively affect their study, stubbornness, disobedience, making trouble to people around and teacher in class, disrespecting the rules, impatience, pugnacity, accident from temerity, aggressiveness, and getting angry easily. As public stigma in children with ADHD will affect their development and their social adjustment, the parents need to cooparute with psychiatrist and interdisciplinary team to heal them. Otherwise, when they are getting older to teenager and adult, most of them will have anti-social behavior and other misbehavior including aggressiveness, harassment, drug addiction, theft, carrying offensive weapons, prostitution, and having risky sexual behavior. These children with ADHD will commit crime, use violence, and will be caught from illegal act more than the regular children.